2012
DOI: 10.1002/nbm.2776
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of response to Vorinostat in an orthotopic rat glioma model

Abstract: Glioblastoma (GBM) is the most common primary brain tumor and is uniformly fatal despite aggressive surgical and adjuvant therapy. Since survival is short, it is critical to determine the value of therapy early on in treatment. Improved early predictive assessment would allow neuro-oncologists to personalize and adjust or change treatment sooner to maximize use of efficacious therapy. During carcinogenesis, tumor suppressor genes can be silenced by aberrant histone deacetylation. This epigenetic modification h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…In this patient population, depression is consistently associated with cognitive impairment, reduced physical function, and poor quality-of-life. Our previous preclinical studies have shown that brain tumors have reduced mI and NAA compared to normal brain, confirming speculation that this may be associated with mood alterations and depression among brain tumor patients [9]. Correlations between elevated mI and NAA levels and improved mood may provide the basis for interventions in the future that improve the quality-of-life of GBM patients.…”
mentioning
confidence: 57%
“…In this patient population, depression is consistently associated with cognitive impairment, reduced physical function, and poor quality-of-life. Our previous preclinical studies have shown that brain tumors have reduced mI and NAA compared to normal brain, confirming speculation that this may be associated with mood alterations and depression among brain tumor patients [9]. Correlations between elevated mI and NAA levels and improved mood may provide the basis for interventions in the future that improve the quality-of-life of GBM patients.…”
mentioning
confidence: 57%
“…Mice treated with vorinostat either intravenously or intraperitoneally showed an increase in histone acetylation (acetyl‐H3 and acetyl‐H4), while proliferation of GL26 murine glioma growth was significantly inhibited . Similarly, a study in rats bearing 9L rat glioma led to a significant reduction of tumor size and a single intratumoral injection of vorinostat doubled the survival of rats bearing GL26 tumors . Based on these and other studies, vorinostat is currently in a Phase I/II clinical trial in combination with TMZ and radiation therapy in newly diagnosed GBM patients (NCT00731731)…”
Section: Introductionmentioning
confidence: 93%
“…Collectively, these data suggest that myoinositol could be a biomarker to quantify response to vorinostat therapy associated with redifferentiation. A preclinical study [42] showed that normalization or restoration of 1 H MRS metabolites could be reliable imaging biomarkers for an early favorable response to vorinostat treatment in an orthotopic animal model for glioma and that reduction in myoinositol and NAA was found to be a potential biomarker for depression, which may also be alleviated with vorinostat treatment.…”
Section: Histone Deacetylase Inhibitor Combined With Standard-of-carementioning
confidence: 99%